Reorientation of Mispositioned Spindles in Short Astral Microtubule Mutant spc72Δ Is Dependent on Spindle Pole Body Outer Plaque and Kar3 Motor Protein - Hoepfner, Dominic (The American Society for Cell Biology, 2002)
Nuclear migration and positioning in Saccharomyces cerevisiae depend on long astral microtubules emanating from the spindle pole bodies (SPBs). Herein, we show by in vivo fluorescence microscopy that cells lacking Spc72, the SPB receptor of the cytoplasmic γ-tubulin complex, can only generate very short (<1 μm) and unstable astral microtubules. Consequently, nuclear migration to the bud neck and orientation of the anaphase spindle along the mother-bud axis are absent in these cells. However, SPC72 deletion is not lethal because elongated but misaligned spindles can frequently reorient in mother cells, permitting delayed but otherwise correct nuclear segregation. High-resolution time-lapse sequences revealed that this spindle reorientation was most likely accomplished by cortex interactions of the very short astral microtubules. In addition, a set of double mutants suggested that reorientation was dependent on the SPB outer plaque and the astral microtubule motor function of Kar3 but not Kip2/Kip3/Dhc1, or the cortex components Kar9/Num1. Our observations suggest that Spc72 is required for astral microtubule formation at the SPB half-bridge and for stabilization of astral microtubules at the SPB outer plaque. In addition, our data exclude involvement of Spc72 in spindle formation and elongation functions.